Waste Management Education for Preventing Infectious Diseases among Coastal Community in Watu Ulo Beach, Jember - Kinanthi, Citra Anggun; Noveyani, Adistha Eka; Simanjuntak, Tri Damayanti (PT. Riset Press International, 2024)
Issues related to waste do not only occur in urban environments. Coastal areas are also not free from issues related to waste. Not only rubbish from the local community but rubbish from tourists also contributes to the large amount of trash in coastal areas. Waste that is not appropriately managed in the environment can be a source of disease. For this reason, it is necessary to increase public knowledge regarding waste processing to prevent the emergence of disease. Apart from that, the public is educated regarding the disease's symptoms and how to treat it. This community service activity occurred in Watu Ulo, Sumberejo Village, Ambulu SubDistrict, Jember Regency. The training was attended by 23 participants who were coastal youth. The results obtained were based on gender; the majority are male, and based on the occupation, the majority are fishermen, and the knowledge of respondents increased after counselling. Conclusion From this training, there has been increased respondents' knowledge through education about waste management socialization.